Anisotropic Rod‐Shaped Particles Influence Injectable Granular Hydrogel Properties and Cell Invasion (Adv. Mater. 12/2022). Issue 12 (24th March 2022) - Qazi, Taimoor H.; Wu, Jingyu; Muir, Victoria G.; Weintraub, Shoshana; Gullbrand, Sarah E.; Lee, Daeyeon; Issadore, David; Burdick, Jason A.
Abstract : Tissue Repair In article number 2109194, Jason A. Burdick and co‐workers report the fabrication of anisotropic rod‐shaped microparticles through a microfluidics approach and their assembly into injectable and porous granular hydrogels for tissue repair. Interconnected and anisotropic pores within these hydrogels support both robust endothelial cell sprouting in vitro and rapid invasion of endogenous cells and blood vessels in vivo.